Unveiling the Potential of AI Assistants: A Review of AI in Building Materials Selection - Wibowo, Andi Prasetiyo (Universitas Atma Jaya Yogyakarta, 2024)
Fast-advancing Artificial Intelligence (AI) has transformed many industries, including construction. AI offers innovative solutions to increase efficiency and effectiveness in various aspects of construction, one of which is selecting building materials. By reading relevant literature, this study aims to determine how much AI can help choose building materials so that projects go more easily and quickly. Using SCOPUS as its principal database, this study conducted a literature review. The method of this study begins with the process of filtering articles using the key string: (